Performance Assessment Of PT. Indofood Sukses Makmur CBP Tbk 2018-2020 Based On Value Creation For Financial Strategy And Investment Decisions - Helmina Ardyanfitri; Eka Mega Pertiwi (Universitas Mercu Buana, 2021)
The Covid-19 condition brought changes to the company's performance and this situation was also felt by PT. Indofood Sukses Makmur CBP, Tbk. Thus, performance appraisal is needed by companies to evaluate and decide policies and take the right strategy. Performance appraisal for public companies can encourage value creation into stable growth, so that companies have good performance both from operations and finance and the public can invest in these companies. The purpose of this study is to assess the company's internal performance in order to assist the company in determining strategies that are appropriate to the company's circumstances and assessing the company's external performance for investment decision making for investors. This research method is a qualitative research with postpositivism method. The results of this study indicate that PT. Indofood Sukses Makmur CBP Tbk in 2018-2020 is in quadrant II in the financial strategy matrix by having a positive value in MVA and being in the excellent value manager quadrant in GVM, so that PT. Indofood Sukses Makmur CBP Tbk is very suitable for long term investment.